Evaluación agronómica de adaptabilidad y rendimiento de 15 cultivares de ajonjolí (Sesamun Índicum L.) en la zona agroecológica de Caluma, provincia Bolívar - Recalde Véloz, Roger Robinson (2015)
Sesame or sesame sedge is more content in seed oils, may vary from 41 to 63% of the total weight thereof, depending on the variety and growing conditions. It may also contain from 17 to 32% protein; 18-20% carbohydrates mainly fibers; essential amino acids including methionine stand. World production in 2004 was 3,092 million tons, which showed growth of 9.5% compared to 2000. America's largest producers are Paraguay, Guatemala, Mexico and Venezuela. In Ecuador it is grown in the provinces of Manabi: Portoviejo; Guayas: Miracle and Pedro Carbo. This research was conducted at the Farm The Triumph of the UEB 350 meters. The objectives in this research were: I. Assess the main agronomic traits of 15 cultivars of sesame. ii.- Select the best cultivars of sesame for the agro-ecological area under study. iii.- generate a database of agronomic characterization of 15 sesame varieties for the agro-ecological zone Caluma. In this study 15 cultivars of sesame complete design Random (RCBD) with 3 replications Blocks Analysis of variance, Tukey test, correlation and regression was performed was applied were evaluated. Treatment with a higher load height was the T13 with 65.07 cm and which had the highest yield was the T14 to 2396.29 kg/ha al 14% humidity. Finally, this study allowed us select promising sesame germplasm for this agro-ecological zone to improve the efficiency of local production systems